A construção discursiva da comunidade do Cajueiro, em São Luís-MA: a disputa pelo espaço e os direitos fundamentais na mídia local - REIS, Ariana Romão dos (2022)
The present work consists of an analysis of the discursive construction of the Comunidade do Cajueiro, a traditional community in the rural area of São Luís, Maranhão, by the local media. We analyzed the statements of journalistic news published electronically in the years 2019 and 2020, especially with regard to violations of fundamental rights of this population. We approach the difficulties of enforcing the fundamental rights of traditional communities in the face of the advances of capitalist enterprises on their territories, taking as an object of analysis the discourses that emerge through the journalistic news that make up the corpus. We aim to identify the enunciative series within what is said about the Community through discursive regularities, as such elements can point to the ways of saying about this collective subject. As the theoretical-methodological perspective, we adopted the archeogenealogical approach to discourse, a method used by Foucault in his studies to understand the mechanisms that articulate different discursive events to the powers of an era. We concluded from the analysis of the archive of speeches produced about the Cajueiro Community that the media speech reflects the struggles of different powers that sometimes clash, sometimes converge with each other in a dispute for the power to enunciate as a form of control of the established discursive order, privileging certain statements and making others invisible. The Community, although able to speak for itself, as an organized collective subject - and at times it is allowed to speak - was massively discursive in the local media by several individuals, from different institutional places, highlighting the media as an important device that produces “truths” and “certainties” within the strategies of control of what is stated.